The Psychological Impact of Melasma on Patients Attending a Tertiary Care Health Facility in Pakistan; A Cross Sectional Study - Noor Ul Wara,; Khan, Qamar Ud Din; Shahid, Muhammad Waseem; Fatima, Kaneez; Ali, Anosh; Fatima, Attiya (Indus Journal of Bioscience Research, 2025)
Objective: This study aims to assess the psychological impact of melasma on patients visiting a tertiary care hospital in Pakistan using DASS-21 scale. Methodology: A cross sectional study was done at Dermatology department, Pak Emirates Military Hospital, Rawalpindi (over the total duration of 6 months (July to Dec, 2024). A total of 392 patients visiting dermatology OPD of Pak Emirates Military Hospital, Rawalpindi were selected via non-probability consecutive sampling technique. Psychological impact of melasma was assessed via a self-reporting questionnaire DASS-21 using Depression, Anxiety and Stress as primary outcomes. Results: The scale identified depression among 22% patients with mean score of 20.5 + 4.3, while rest of patients exhibit no or very little sign of depression. Anxiety was observed in 28% patients with mean score of 16.2 + 3.8, and stress was reported in 37% of patients with mean score of 22.7 + 4.9. Correlation between mean DASS-21 score of patients and duration of disease was found significant. Conclusion: Melasma patients experience significant impairment on quality of life. These symptoms appear to be related with duration of melasma. It is essential for health care providers to acknowledge and evaluate the psychological impact of melasma when counselling and treating the patients.